27 The DiPEP (Diagnosis of PE in Pregnancy) study: can clinical assessment, d-dimer or chest x-ray be used to select pregnant or postpartum women with suspected PE for diagnostic imaging?. Issue 12 (23rd November 2017) - Goodacre, Steve; Horspool, Kimberley; Nelson-piercy, Catherine; Knight, Marian; Shephard, Neil; Lecky, Fiona; Thomas, Steven; Hunt, Beverley; Fuller, Gordon
Abstract : Objective: To determine whether clinical features (in the form of a clinical decision rule) or d-dimer can be used to select pregnant or postpartum women with suspected PE for diagnostic imaging. Design: Observational cohort study augmented with additional cases. Setting: Consultant-led maternity units participating in the UK Obstetric Surveillance System (UKOSS) and emergency departments and maternity units at eleven prospectively recruiting sites. Participants: 198 pregnant or postpartum women with diagnosed PE identified through UKOSS and 324 pregnant or postpartum women with suspected PE from prospectively recruiting sites. Interventions: Data were collected relating to clinical features, elements of clinical decision rules, d-dimer measurements, diagnostic imaging, treatment for PE and adverse outcomes. Main outcome measures: Women were classified as having or not having PE on the basis of diagnostic imaging, treatment and subsequent adverse outcomes. Primary analysis was limited to women with conclusive diagnostic imaging. Secondary analyses included women with clinically diagnosed or ruled out PE. Results: The primary analysis included 181 women with PE and 259 without. Most clinical features showed no association with PE. The only exceptions were number of previous pregnancies over 24 weeks (p=0.017), no varicose veins (p=0.045), no recent long haul travel (p=0.006), recent surgery including caesarean section (p=0.001), increased temperature (p=0.003), low oxygen saturation (p<0.001), PE-related chest x-ray abnormality (p=0.01) and other chest x-ray abnormality (p=0.001). Clinical decision rules had areas under the receiver-operator characteristic curve ranging from 0.577 to 0.732. No clinically useful threshold for decision-making was identified for any rule. The sensitivities and specificities of d-dimer were 88.4% and 8.8% using the standard laboratory threshold and 69.8% and 32.8% using a pregnancy-specific threshold. Conclusions: Clinical decision rules, d-dimer and chest x-ray should not be used to select pregnant or postpartum women with suspected PE for diagnostic imaging.